A separator modified by barium titanate with macroscopic polarization electric field for high-performance lithium–sulfur batteries. Issue 12 (6th March 2023) - Ma, Li; Zhang, Youquan; Zhang, Chunxiao; Zhu, Hai; Zhang, Shuai; Yan, Mingyang; Liang, Chaoping; Zhang, Yan; Chen, Yuejiao; Chen, Libao; Wei, Weifeng; Zhou, Liangjun
Abstract : The configuration of positive charge alignments in a poled-BaTiO3 functionalized separator, and the mechanism for anchoring polysulfides and accelerating Li-ion transportation. Abstract : The detrimental "shuttling effect" of lithium polysulfides and the sluggish kinetics of the sulfur redox reaction in lithium–sulfur batteries (LSBs) impede the practical application. Considering the high polar chemistry facilitates the anchoring of polysulfides, ferroelectric materials have gradually been employed as functionalized separators to suppress the "shuttling effect". Herein, a functional separator coated with BaTiO3 with a macroscopic polarization electric field (poled-BaTiO3 ) is designed for retarding the problematic shuttle effect and accelerating redox kinetics. Theoretical calculations and experiments revealed that resultant positive charged alignments on the poled-BaTiO3 coating can chemically immobilize polysulfides, effectively improving the cyclic stability of LSBs. Moreover, the simultaneous reinforcement of the built-in electric field in the poled-BaTiO3 coating can also improve Li-ion transportation for accelerating redox kinetics. Benefiting from these attributes, the as-developed LSB attains an initial discharge capacity of 1042.6 mA h g −1 and high cyclic stability of over 400 cycles at 1 C rate. The corresponding LSB pouch cell was also assembled to validate the concept. This work is anticipated to provide new insight into the development of high-performing LSBs through engineering ferroelectric-enhanced coatings.